2015
DOI: 10.1371/journal.pone.0121238
|View full text |Cite
|
Sign up to set email alerts
|

Physical Education: The Effect of Epoch Lengths on Children’s Physical Activity in a Structured Context

Abstract: BackgroundDespite a consensus emerging that affirms that shorter epochs should be used in youth to correctly register physical activity levels in free-living conditions, little is known about its effect on children’s physical activity conducted in structured periods of time. This study analyzed the effect that epoch length (1, 2, 3, 5, 10, 15, 30 and 60s) may have on different physical activity intensities in physical education lessons.MethodsA sample of 1912 individual measures of physical education lessons w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 23 publications
3
33
0
1
Order By: Relevance
“…Furthermore, in our experience, children and youth are frequently asked to remove devices during sports by teachers or coaches, which makes completion of a burdensome and unpopular activity diary necessary for the most accurate physical activity measurement. The application of accelerometers requires specialist software and technical expertise; devices are not interexchangeable, and data processing decisions, such as epoch length (interval over which acceleration signals are averaged), can significantly impact the results, especially in children who have sporadic bursts of high-intensity activity 24. Further, there are currently several cut points available to categorise moderate-to-vigorous physical activity for children using the ActiGraph device alone 25.…”
Section: Physical Activity Monitorsmentioning
confidence: 99%
“…Furthermore, in our experience, children and youth are frequently asked to remove devices during sports by teachers or coaches, which makes completion of a burdensome and unpopular activity diary necessary for the most accurate physical activity measurement. The application of accelerometers requires specialist software and technical expertise; devices are not interexchangeable, and data processing decisions, such as epoch length (interval over which acceleration signals are averaged), can significantly impact the results, especially in children who have sporadic bursts of high-intensity activity 24. Further, there are currently several cut points available to categorise moderate-to-vigorous physical activity for children using the ActiGraph device alone 25.…”
Section: Physical Activity Monitorsmentioning
confidence: 99%
“…The problem with the MVPA measurement during intermittent activities comes mainly from the sampling interval, also called epoch length-an epoch representing the length of time during which activity counts (a measure of activity magnitude) are summed before being stored by the accelerometer -. Indeed, it is now well established that the selection of different epoch lengths during data processing leads to different MVPA scores [12][13][14][15][16][17]. Among these studies, some observed a decrease in MVPA scores as the epoch lengths increase [13][14][15] while others found the opposite with an increase in MVPA with longer epoch lengths [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is now well established that the selection of different epoch lengths during data processing leads to different MVPA scores [12][13][14][15][16][17]. Among these studies, some observed a decrease in MVPA scores as the epoch lengths increase [13][14][15] while others found the opposite with an increase in MVPA with longer epoch lengths [16,17]. It is therefore difficult to establish a general rule, especially since a common limitation of all these studies is the lack of measurement criterion, such as direct observation, thus preventing comparison and determination of which epoch length is actually the most accurate to estimate PA.…”
Section: Introductionmentioning
confidence: 99%
“…Epoch lengths of 1-s will be used to provide a more accurate representation of students’ activities [45, 46]. The percentages of time students spent in moderate and vigorous activities will be summed as a measure for MVPA.…”
Section: Methodsmentioning
confidence: 99%